Examining the Concept of Educational Leadership from the Classical Islamic Worldview - Imran H Khan Suddahazai (UIN Sunan Gunung Djati Bandung, 2023)
-This article explores the concept of leadership from the perspective of the Islamic worldview. It begins by emphasizing the fundamental belief in Allah's Oneness and Supreme nature and the purpose of human beings as servants to serve Allah. The relationship between God and humans is based on followership, with every individual considered a unique creation with an exclusive bond to Allah (sbt) as the only true leader. The article highlights the idea of equality in Islamic thought, where individuals are seen as equals but undergo trials to test their characters and facilitate personal growth. It further discusses how individuals striving for virtuous Knowledge can attain positions of respect and recognition, emphasizing that leadership is determined by the extent to which individuals realize their latent potentialities. The article also explores the dialectical approach, which harmonizes seemingly contradictory notions and prevents the fragmentation of self, thought, values, and norms. It emphasizes the Importance of learning from divergent opinions and acknowledges the constant need for assessing and reformulating theory and practice. The concept of education is deeply rooted in the Islamic worldview, encompassing the holistic developmental progression of individuals based on their Knowledge and understanding of creation. The article concludes by asserting that leadership in the Islamic worldview involves actively witnessing faith in action and integrating secular and divine Knowledge. It highlights the dialogical-dialectical process through which educational leaders guide their followers towards continual self-development. Overall, this article provides insights into the understanding of leadership derived from the Islamic worldview.